Analysis of risk factors for non-sentinel lymph node metastasis in patients with sentinel lymph node-negative breast cancer - ZHANG Fengzhe, TONG Yiwei, CHEN Xiaosong, SHEN Kunwei (Waike lilun yu shijian)
Objective To analyze the risk factors for non-sentinel lymph node (NSLN) metastasis in patients with sentinel lymph node (SLN)-negative breast cancer. Methods Patients with breast cancer who underwent mastectomy and SLN biopsy at our center between January 2009 and August 2024 were retrospectively included. Univariate and multivariate analyses were performed in SLN-negative populations underwent low axillary lymph node dissection to identify risk factors for NSLN metastasis. Results A total of 2 387 SLN-negative patients were included, including 2 288 (95.9%) without NSLN metastasis and 99 (4.1%) with NSLN metastasis. Univariate and multivariate analyses showed that lymphovascular invasion (LVI) was an independent risk factor for NSLN metastasis in SLN-negative patients (13.5% versus 3.5%; OR=4.14，95% CI: 2.27-7.56，P<0.001). Patients with multicentric breast cancer showed a trend towards higher risk of NSLN metastasis compared to other types of breast cancer (9.5% versus 4.1%; OR=2.08，95% CI： 0.90-4.81，P=0.089). Conclusions Patients with SLN-negative biopsy who have LVI or multicentric breast cancer are at higher risk for NSLN metastasis.